2022
DOI: 10.1111/jonm.13608
|View full text |Cite
|
Sign up to set email alerts
|

Professional identity and emotional labour affect the relationship between perceived organisational justice and job performance among Chinese hospital nurses

Abstract: Aim: To investigate the influence of perceived organisational justice, professional identity and emotional labour on nurses' job performance.Background: Previous studies have not explored the impact of professional identity and emotional labour on the relationship between perceived organisational justice and job performance. However, how to mobilize the enthusiasm of nurses and improve their job performance is the key for nursing managers to realize the sustainable development of hospitals.Methods: A cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 43 publications
4
22
0
Order By: Relevance
“…The results of this survey showed that 952 nurses scored 29.74±8.45 on the professional identity scale, which is at a moderate level and is generally consistent with the results reported by a previous study involving 412 nurses in public psychiatric hospitals in Shanghai 38. Similarly, the results aligned with the level of professional identity of nurses in general hospitals 39. Psychiatric patients have several abnormal behaviours and actions, such as wandering, violence and aggression, self-harm, suicide, absconding and choking, which require close observation, constant assessment and response by psychiatric nurses in their daily work.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of this survey showed that 952 nurses scored 29.74±8.45 on the professional identity scale, which is at a moderate level and is generally consistent with the results reported by a previous study involving 412 nurses in public psychiatric hospitals in Shanghai 38. Similarly, the results aligned with the level of professional identity of nurses in general hospitals 39. Psychiatric patients have several abnormal behaviours and actions, such as wandering, violence and aggression, self-harm, suicide, absconding and choking, which require close observation, constant assessment and response by psychiatric nurses in their daily work.…”
Section: Discussionsupporting
confidence: 89%
“… 38 Similarly, the results aligned with the level of professional identity of nurses in general hospitals. 39 Psychiatric patients have several abnormal behaviours and actions, such as wandering, violence and aggression, self-harm, suicide, absconding and choking, which require close observation, constant assessment and response by psychiatric nurses in their daily work. These behaviours and responses can increase nurses’ tension and further exacerbate pre-existing work stress, thus affecting the level of professional identity.…”
Section: Discussionmentioning
confidence: 99%
“…Herzberg’s two-factor theory suggests that incentives can produce a sense of achievement, identity, and responsibility [ 66 ]. Yu’s study also showed that professional identity, emotional labor, and job performance were positively correlated [ 67 ]. Above all, out study suggested to pay attention to employees’ emotional labor skills training, negative emotions management and policy support and technical guidance provision to help boost positive emotions at work, which in turn increases job satisfaction and career success.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, academic procrastination can also drain students and prevent them from learning more nursing knowledge and skills [ 11 ], which is detrimental to training more nurses and improving the quality of nursing education around the world. At present, growing demand for nursing and increasing global difficulties in recruiting and retaining nurses are undermining nursing outcomes worldwide [ 12 , 13 ]. Therefore, it is critical to cultivate more professional and enthusiastic nursing students.…”
Section: Introductionmentioning
confidence: 99%